A descontrução e reconstrução dos modelos parentais intergeracionais através do sociodrama construtivista - Castello, Ana Lúcia Gomes (2006)
In this study, the author seeks to present a new form of parental guidance, called Constructivist Socio-drama, for bringing up children. Based on the general current view that the process of bringing up children has become an obstacle race in addition to one having to assume other roles within the family boundaries, for which parents have not been trained -, husbands and wives are faced with increasing difficulties to transmit to their children basic breeding concepts, or even direct the breeding process towards a positive construction of the emotional, social and family identity. The main purpose of this work is to enable parents, by means of group sessions, to understand the inter-generational transmission in the breeding strategies, and to reconstruct those strategies deemed inadequate. Firstly, the author takes a theoretical approach to parenthood in post-modern ages, conducts a study of the historical aspects related to the process of bringing up children in Brazil, and finally a synthesis of parental role-models in different contexts. Bringing up children in different social levels and the development theory of families during the three phases of the vital cycle, namely, the formation of the couple, families with small children and families with adolescents, are chapters that elicit the theoretical body of this research. The author then reflects on the repetition of inter-generational role-models and on modern family themes, which were approached by means of questionnaires previously applied to each parent, and based on the answers they provided. In order to achieve the proposed goals, a qualitative study was conducted through Constructivist Socio-dramas with groups of parents. Such Constructivist Socio-dramas are described in their peculiarities as an instrument to be used for articulation, elaboration and review of the constructions used by human beings to reorganize their experiences and actions. In this study, the author also deployed a questionnaire to gather data on the difficulties parents face in bringing up their children. Fifteen Socio-dramas were conducted in different places: at a Pediatrics Clinic and at an NGO, both in São Paulo, and they were filmed and photographed upon authorization of the participants. Based on the narratives produced at the Constructivist Socio-dramas, the data analysis points towards an image of parents seeking behavioral and emotional growth in bringing up their children. It also points towards the perception of inter-generational repetitious situations, which were revised and made it possible to elaborate new models for the performance of the parental role